Genomic Insights into the Distribution and Phylogeny of Glycopeptide Resistance Determinants within the Actinobacteria Phylum - Andrés Andreo-Vidal; Elisa Binda; Victor Fedorenko; Flavia Marinelli; Oleksandr Yushchuk (Antibiotics, 2021)
The spread of antimicrobial resistance (AMR) creates a challenge for global health security, rendering many previously successful classes of antibiotics useless. Unfortunately, this also includes glycopeptide antibiotics (GPAs), such as vancomycin and teicoplanin, which are currently being considered last-resort drugs. Emerging resistance towards GPAs risks limiting the clinical use of this class of antibiotics—our ultimate line of defense against multidrug-resistant (MDR) Gram-positive pathogens. But where does this resistance come from? It is widely recognized that the GPA resistance determinants—van genes—might have originated from GPA producers, such as soil-dwelling Gram-positive actinobacteria, that use them for self-protection. In the current work, we present a comprehensive bioinformatics study on the distribution and phylogeny of GPA resistance determinants within the Actinobacteria phylum. Interestingly, van-like genes (vlgs) were found distributed in different arrangements not only among GPA-producing actinobacteria but also in the non-producers: more than 10% of the screened actinobacterial genomes contained one or multiple vlgs, while less than 1% encoded for a biosynthetic gene cluster (BGC). By phylogenetic reconstructions, our results highlight the co-evolution of the different vlgs, indicating that the most diffused are the ones coding for putative VanY carboxypeptidases, which can be found alone in the genomes or associated with a vanS/R regulatory pair.